Qualitative investigation of athletes' perceptions of cheating in sport - Saulius Šukys; Diana Karanauskienė; Jolita Šmigelskaitė (Lithuanian Sports University, 2019)
Background. The aim of the present study was to give voice to elite athletes exploring their perceptions of cheating in sport. Methods. Utilizing a purposeful sampling technique, 11 athletes were interviewed - one woman and 10 men from football (F, n = 6), rugby league (R, n = 2), and three from athletics (A). Athletes' perceptions related to cheating in sport were explored by individual semi-structured interviews. Interpretive thematic data analysis was conducted in several stages, beginning with the exploration of the recorded materials. Credibility of the results was established by member checking. For data transferability and repeatability, we described the process of data collection, processing and analysis in detail. Results. Analysis of interview data allows to distinguish the following broad themes: the perceived forms of cheating in sport, causes of cheating, initiators of cheating, and ath-letes' views on the evaluation of cheating, and as a separate theme - athletes' insights on cheating in children's sport. Conclusions. The findings offer insights of adult athletes on cheating in sport. Athletes are aware of the prevalence of cheating in all sports, emphasizing that it is an illegal phenomenon and associate it with the potential financial benefits, corruption, match fixing, and the use of doing. The study highlights financial insecurity of athletes as a reason for cheating. When evaluating cheating, athletes are not categorical or tend to cheat themselves, but they would justify it more if it helped a team. As to cheating in children's sport, adult athletes noted the role of a coach and especially the parents in cheating in order to gain an advantage for their child. Also, the focus on the protective factor of children against cheating was emphasized.  Keywords: cheating, athletes' perceptions, adult sport, children sport.